Acute Pain in the African Prehospital Setting: A Scoping Review. (16th April 2019) - Lourens, Andrit; McCaul, Michael; Parker, Romy; Hodkinson, Peter
Abstract : Background . Acute pain is a common reason for seeking prehospital emergency care. Regrettably, acute pain is often underestimated and poorly managed in this setting. The scoping review was conducted to gain insight into existing research on the topic and to make recommendations for future work. Objectives . To identify all available evidence related to acute pain assessment and management in the African prehospital setting, describe the extent of the evidence, encapsulate findings, and identify research gaps. Methods . The scoping review considered primary and secondary research related to acute pain assessment and management of both medical and traumatic origins in all age groups in the African prehospital setting. The search strategy aimed to identify published, unpublished, and ongoing research which met the inclusion criteria. Potentially eligible studies were identified by a comprehensive search of electronic databases, trial registers, dissertation/thesis databases, grey literature databases, and conference proceedings. Screening and data extraction were conducted independently and in duplicate. Results . The comprehensive search identified 3823 potential studies, duplicate titles were removed, and 3358 titles/abstracts were screened. Full text of 66 potentially eligible titles was screened, 60 were excluded, and six publications met the inclusion criteria. Despite recommendations for pain assessment during general patient care, most studies reported no/limited pain assessment. In general, pain management was concluded to be insufficient and not conforming to best practice. Conclusions . Only six publications addressing prehospital acute pain care in Africa could be identified, possibly indicative of a knowledge gap. Future research is indicated to enable a better understanding of the epidemiology of acute pain and barriers and enablers of acute pain care and to develop evidence-based clinical practice guidelines (CPGs) catering for all EMS systems in Africa. Additionally, educational initiatives should be implemented to improve the quality of acute pain care and to monitor quality through continuous quality improvement (CQI) programs.